Loet Leydesdorff, the Triple Helix and ways to capture societal impact—a tribute - Meyer, Martin (Springer, 2025)
Much can be said about the seminal contributions Loet Leydesdorff has made overall to the literature on science & technology indicators and innovation. Many have already highlighted the legacy that Loet has left behind (e.g., Amaral et al in Triple Helix 10:161–187, 2024). This note sets out to pay tribute to the contributions Loet has made in the space of Triple Helix, indicators, and societal impact by developing frameworks and models that bridge quantitative, information-driven and qualitative social sciences.
Keywords: Loet Leydesdorff; Key word analysis; Co-authorship analysis; fi=InnoLab|en=InnoLab|